2019
DOI: 10.3390/molecules24122240
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomics in Metal-Based Drug Research

Abstract: Thanks to recent advances in analytical technologies and statistical capabilities, the application field of metabolomics has increased significantly. Currently, this approach is used to investigate biological substrates looking for metabolic profile alterations, diseases markers, and drug effects. In particular, NMR spectroscopy has shown great potential as a detection technique, mainly for the ability to detect multiple (10s to 100s) metabolites at once without separation. Only in recent years has the NMR-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 81 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…The deleterious effects of Pt-drugs have triggered the development of complexes [ 9 , 16 ] with transition-metal centers such as palladium(II), gold(I)/(III), and ruthenium(II)/(III) [ 8 , 17 , 18 ]. Pd(II) has been recognized as one of the best candidates due to its physical-chemical similarities to Pt(II) [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deleterious effects of Pt-drugs have triggered the development of complexes [ 9 , 16 ] with transition-metal centers such as palladium(II), gold(I)/(III), and ruthenium(II)/(III) [ 8 , 17 , 18 ]. Pd(II) has been recognized as one of the best candidates due to its physical-chemical similarities to Pt(II) [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further metabolic perturbations produced in vitro and in vivo (both locally (tissues) and systemically (biofluids)) are detectable by metabolomics and may pave the way for defining possible new markers of drug toxicity, efficacy, or resistance [ 46 , 47 ]. Unlike for cisplatin [ 48 , 49 , 50 ], the effects of Pd(II)-complexes have rarely been evaluated by metabolomics [ 16 ], to the best of our knowledge, with a single report comprising the impact of Pd 2 Spm complex on human osteoblasts (HOb) and osteosarcoma (MG-63) cells using nuclear magnetic resonance (NMR)-based metabolomics [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…During these years, the clear role of specific metabolic pathways in driving pro-tumorigenic events including tumor growth, chemoresistance and plasticity, is emerged [19][20][21][22][23][24]. An over-expression of metabolic genes regulating glycolysis, aminoacyl-tRNA biosynthesis, pyrimidine biosynthesis, purine biosynthesis and pentose phosphate pathway characterize tumor tissues compared to normal samples, thus highlighting the hypothesis of a specific metabolic signature at the tumor level [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, this approach revealed that Pd 2 Spm can impact differently on cell metabolism (of both cancer and healthy cells), depending on whether it is administered alone or combined with other drugs. In fact, the promise of such strategies in revealing hidden features of cellular response to metal complexes with potential anti-cancer action has been recently reviewed, giving particular emphasis to NMR as the chosen analytical technique ( 32 ).…”
Section: In Vitro Studies Of the Metabolic Impact Of Pd(ii) mentioning
confidence: 99%